Teacher Retention and Leadership Qualities: A Study of Teachers’ Job Satisfaction in the US and UK - Wadsley, Kerry (2017)
The aim of this dissertation was to identify the factors causing teacher turnover and teacher retention in relation to school leaders. To do this, the researcher examined the key factors found in previous literature and studies on retention and teacher turnover, concluding that there was a strong relationship between school leadership and teacher retention. This study was conducted using a mixed-methods approach, aiming to identify key factors for school leaders with regards to retention. Research methods included a questionnaire and two follow up focus groups. The results of this study confirmed the findings in previous literature, signifying the importance of school leaders on teacher retention. Furthermore, the results of this study identified seven key elements that influenced teachers’ job satisfaction and consequently their retention. Suggestions for school leaders and points for further discussion are made in conclusion.